Eutrophica of The Strzeszyńskie Lake: sources, consequence and remedies = Eutrofizacja Jeziora Strzeszyńskiego: źródła, konsekwencje i środki zaradcze - Zawadzki, Pawel; Murat-Błażejewska, Sadżide; Błażejewski, Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents history and recent review of investigations on ecological status of the Strzeszyńskie Lake, located within borders of town Poznań. The lake is a popular rest place, also for bathing and angling, therefore its state concerns many institutions and inhabitants. Recently, a deterioration of its ecological state has been observed due to pollution from a tributary catchment (Row Złotnicki), lake?s direct catchment, precipitation and fallen leaves. Phosphorus balance for an average year was estimated. A review of applied remedies was provided but an assessment of their effectiveness was unfeasible due to simultaneity and relatively short duration of their application.
Keywords: eutrofizacja; bilans fosforu; zanieczyszczenia obszarowe; eutrophication; phosphorus balance; diffuse pollution